(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Gynecology is the medical practice dealing with the health of the female reproductive system literally means the science of women. Woman has a unique existence in the universe created by the God. Womens health is the pivot not only for the healthy and happy status for her family, rather to the whole society or even to the nation at large. All women have experienced some short of vaginal discharge in her life span. White vaginal discharges along with the other symptoms like feeling of weakness, pain in the back and calves, loss of vital fluids, pruritis on and around the vulva, thighs and thigh joints etc., comes under the heading of Leucorrhoea, which is described as Sweta Pradara in Ayurvedic classics. In Samhitas all gynecological disorders comes under the headings of Yonivyapada. No any description of Sweta Pradara has been described by scholars of Brihatrayee. For abnormal white vaginal discharges, the word Sweta Pradara has been described in texts during and after medieval period.